Commencing colorectal cancer screening at age 45 years in U.S. racial groups - Carethers, John M. (Frontiers in Oncology, 2022)
Screening for colorectal cancer (CRC) is cost-effective for reducing its mortality among the average-risk population. In the US, CRC incidence and mortality differ among racial/ethnic groups, with non-Hispanic Blacks (NHB) and American Indian/Alaska Natives showing highest incidence and mortality and earlier presentation. Since 2005, some professional societies have recommended CRC screening for NHB to commence at 45 years or earlier; this was not implemented due to lack of recommendation from key groups that influence insurance payment coverage. In 2017 the highly influential U.S. Multi-Society Task Force for Colorectal Cancer recommended screening to commence at 45 years for NHB; this recommendation was supplanted by data showing an increase in early-onset CRCs in non-Hispanic Whites approaching the under-50-year rates observed for NHB. Subsequently the American Cancer Society and the USPSTF recommended that the entire average-risk population move to commence CRC screening at 45 years. Implementing screening in 45–49-year-olds has its challenges as younger groups compared with older groups participate less in preventive care. The US had made extensive progress pre-COVID-19 in closing the disparity gap for CRC screening in NHB above age 50 years; implementing screening at younger ages will take ingenuity, foresight, and creative strategy to reach a broader-aged population while preventing widening the screening disparity gap. Approaches such as navigation for non-invasive and minimally invasive CRC screening tests, removal of financial barriers such as co-pays, and complete follow up to abnormal non-invasive screening tests will need to become the norm for broad implementation and success across all racial/ethnic groups.